Professionalism and acting in Zimbabwe: case study of fair take media. - Musana, Arnold S. (Midlands State University, 2017)
This research is an investigation on the professionalism and acting levels in Zimbabwe, a case study of Fair Take Media. The research looks at the acting approaches that are used in Zimbabwe and as well in developed countries, their similarities and how they have been implemented in the Zimbabwean film industry as compared to the other competitive film industries around the globe. Most importantly, this study also exhausts the ways of improving these methods in the Zimbabwean film industry so as to develop to a better stage where the industry produces globally competitive films and plays as well as putting Zimbabwe on the spotlight to other countries. Therefore there is an analysis of the acting techniques, their importance and how they are implemented in Zimbabwean film industry.